The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/tea.21595
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning about genetic mechanisms: Affordances and constraints for learning

Abstract: Mechanisms are central in scientific explanations. However, developing mechanistic explanations is difficult for students especially in domains in which mechanisms involve abstract components and functions, such as genetics. One of the core components of genetic mechanisms are proteins and their functions. Students struggle to reason about the role of proteins while learning genetics and show limited ability to provide mechanistic explanations of genetic phenomena. In genetics education there are currently two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 54 publications
3
23
0
Order By: Relevance
“…This suggests that knowledge about proteins may be useful for reasoning about mechanisms of phenotypic plasticity. This is in line with growing evidence over the past decade stressing the importance of learning about protein functions in order to support reasoning about a wide variety of genetic phenomena (e.g., Duncan et al, 2011;Todd and Kenyon, 2016;Todd et al, 2019;van Mil et al, 2016;Haskel-Ittah and Yarden, 2017;Haskel-Ittah et al, 2019). Additionally, we found that students also invoked ideas about regulation of gene expression and that such ideas were useful in fleshing out explanations about short-and long-term phenotypic plasticity changes.…”
Section: Two Mechanistic Accounts For Phenotypic Plasticitysupporting
confidence: 88%
See 1 more Smart Citation
“…This suggests that knowledge about proteins may be useful for reasoning about mechanisms of phenotypic plasticity. This is in line with growing evidence over the past decade stressing the importance of learning about protein functions in order to support reasoning about a wide variety of genetic phenomena (e.g., Duncan et al, 2011;Todd and Kenyon, 2016;Todd et al, 2019;van Mil et al, 2016;Haskel-Ittah and Yarden, 2017;Haskel-Ittah et al, 2019). Additionally, we found that students also invoked ideas about regulation of gene expression and that such ideas were useful in fleshing out explanations about short-and long-term phenotypic plasticity changes.…”
Section: Two Mechanistic Accounts For Phenotypic Plasticitysupporting
confidence: 88%
“…Based on our own prior work, we propose that these decisions depend on domain-specific knowledge of appropriate entities (and their activities) in the domain (Duncan, 2007;Haskel-Ittah et al, 2019). For example, when we asked seventh-grade students to explain the effect of genes on certain traits, they used the entity "protein" only in cases in which they knew of a relevant protein activity that could account for the formation of the trait in question.…”
Section: Introductionmentioning
confidence: 99%
“…Students have issues with understanding the relationship between genes and observed traits and more specifically how the synthesized proteins are involved in the expression of traits (Thörne & Gericke, 2014). The ability to reason about genetic principles is important for general scientific literacy, for example, to understand genetically modified organisms (Haskel-Ittah et al, 2019).…”
Section: Scientific Reasoningmentioning
confidence: 99%
“…Although proteins are not genetic material, they are involved as components that regulate the genetic expression of many genes. However, many students have difficulty understanding the involvement of proteins in trait determination mechanisms (Haskel-Ittah & Yarden, 2017;Haskel-Ittah et al, 2020;Thörne et al, 2013). Therefore, to ensure and evaluate student literacy more thoroughly, this concept also needs to be accessed.…”
Section: Discussionmentioning
confidence: 99%